Assessment of a website aimed at providing information on mental health to secondary school students in Can Tho city, Vietnam - Dat Tan Nguyen; Tam Thi Pham; E. Pamela Wright; Joske Bunders (BMC, 2021)
Abstract Background The stigmatization of mental health problems is a primary barrier for young people to approach mental health services when they suspect they might have such problems. Nevertheless, the internet has become a common platform on which they are likely to seek information on mental health. As such, this study aimed to explore responses from secondary school students in Can Tho city regarding suckhoetre.vn website. This website provided information on health and mental health, and this study assessed the potential relevance, appeal, accessibility, usefulness, and sustainability of the website. Methods A cross-sectional study included 643 secondary school students in Can Tho city selected by cluster sampling. Two weeks after the students were introduced to the website, they were invited to evaluate it using an anonymous questionnaire. The Chi-squared test was used to assess the significance of differences in the distribution of selected students' sociodemographic characteristics. Results Most (98.6%) participants visited the website in the two-week period, 74% once or twice a week, the others more often, up to once a day. Their activities included reading information (85.8%), seeking help (17.7%), sharing information (15.5%), giving advice to others (11.0%), and chatting or giving comments (9.8%). Most students rated the website very highly in terms of appeal, relevance, accessibility, and usefulness, and wanted to have access to the website in the future. These findings are positive signals to pursue the possible use of a website on mental health for secondary school students to help raise awareness and support good mental health among adolescents in Can Tho city and beyond. Conclusion A website designed to provide information to secondary school students appeared to be a promising way to provide access to information on the topic of mental health. The website should be maintained and introduced widely to students, teachers and parents, with regular evaluation of the effectiveness of this website.